Rancang Bangun Sistem Informasi Inventaris Peralatan Broadcast TVRI Sumatera Utara Berbasis Web - Zubaidah Zubaidah; Nurhasanah Tambunan; Rifani Khairani Pohan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This research aims to design and build a web-based broadcast equipment inventory information system at TVRI North Sumatra. This information system was developed to overcome existing inventory management problems, such as tracking, managing and maintaining broadcast equipment. The development method used includes requirements stages, system design analysis, implementation, and testing using the black box method. This system was built using PHP as the programming language, MySQL as the database, and CSS and JavaScript for the user interface. Test results show that this system can manage equipment inventory effectively, including the functions of borrowing, returning and maintaining equipment. This system also allows integration with other existing systems at TVRI and provides long-term benefits such as increasing data accuracy and operational efficiency. The implementation of this information system is expected to support smooth operations and improve the quality of inventory management at TVRI North Sumatra.